Piloting Per-Student Formula Financing in Moldova : First Outcomes and Policy Recommendations - World Bank (Washington, DC, 2014)
At present, the education sector is characterized by an oversized network of increasingly small schools and a high number of poorly paid teachers and non-teaching staff. A recent Ministry of Education sponsored feasibility study concluded that up to half of Moldova s rural schools may need to be reorganized in the next three to five years in order to counteract the sharp population declines that have taken place over the last 20 years. It is important to underline that the restructuring of the school network is not a goal in itself. The main purpose of the reforms will be to improve quality of education through consolidation of schools and better utilization of resources, human and physical. The results of the evaluation of the pilots (first two-years of implementation for which the data is available) have been presented and discussed with the Ministry of Education during the Bank missions in May and September 2012. This paper is organized as follows: section two explains sector context and the core of the per student financing reforms. Section three highlights key milestones in per student financing reform in Moldova. Section four reviews first outcomes of per-student finance in two pilots Riscani and Causeni. Finally, section five presents the summary of key findings and policy recommendations.